Perimenopausal syndrome and hypertension during perimenopause in South China: prevalence, relationships and risk factors - Zheng Li; Jun-Ping Guo; Liu Huang (BMC, 2024)
Abstract Background More than 2 billion women are experiencing the menopausal transition in China, and some of these women have hypertension. Limited studies has focused on perimenopausal syndrome and hypertension in a specific population, so we aimed to investigate the prevalence of perimenopausal syndrome and hypertension and to analyse their relationships and risk factors in perimenopausal women in South China. Methods This cross-sectional study included 3553 women aged 40 to 60 years from South China. We collected medical report, lifestyle, blood sample, general condition questionnaire, and modified Kupperman index (mKMI) data. Multivariate logistic regression analysis was performed to identify risk factors for perimenopausal syndrome and hypertension during perimenopause. Results The prevalence of hypertension in perimenopause patients was 16.58%, and the prevalence of perimenopausal syndrome was 9.9%. Compared with women without hypertension during perimenopause, women with HTN during perimenopause had an increased risk of perimenopausal syndrome (26.4% vs. 8.7%, P < 0.001). Lipid levels and urinary tract infections were risk factors for hypertension and perimenopausal syndrome, in addition to the presence of breast nodules, the intake of snacks at night, high-salt diets, red meat and sugar-sweetened beverages, and a history of smoking and drinking for perimenopausal syndrome and the presence of gestational hypertension and diabetes for hypertension. Conclusion We concluded that perimenopausal syndrome and HTN are common in perimenopausal women in South China, and the associations between them are strong and positive. Perimenopausal syndrome shares some common risk factors with HTN during perimenopause, such as BMI and dyslipidaemia. Therefore, gynaecological endocrinologists in China should consider screening for perimenopausal syndrome in hypertensive perimenopausal women, and appropriate management of perimenopause is needed to alleviate these conditions.